Gestión administrativa financiera y su repercusión en la rentabilidad de la ferretería Domínguez periodo 2013-2014, Modelo de gestión. - Gomezcoello Yépez, Héctor Enrique (2015)
Ferretería Domínguez emerged two decades ago, today account with three agencies in the Quevedo City, which are distributed in the central part of the city and is the matrix, and the others, in the Parroquia San Camilo and the Parroquia Siete de Octubre. The overall objective of this research consists of determining the incidence of financial administrative management in obtaining the profitability of Ferretería Domínguez. The general hypothesis of this research is presented in the following way: The inadequate financial administrative management affects the growth and organizational development of Ferretería Domínguez. Employees, managers and executives of the company mostly expressed that its management results are excellent and very good, however a financial level and in most of the indicators the results are adverse and profitability rates are below the cost of opportunity and market capital. Preferred way, the promotion of competitiveness and innovation have been the strategies used to achieve the best financial results, but the analysis carried out shows that they have not had an effect in the organization. The 60% employees, managers and executives considered that it is necessary to change the model of management, with the aim of improving the profitability of the company, while the 67.1% is agreed that this change.